2006
DOI: 10.1680/ensu.2006.159.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable supply chains for rural water supplies in Africa

Abstract: Many rural water supplies in sub-Saharan Africa demonstrate high operational failure rates, particularly those using handpumps to extract groundwater. The supply of spare parts for pump maintenance is one of the weak links in the quest for sustainability and there are very few examples of sustainable supply chains throughout the subcontinent. There are a number of key reasons for this, which are specific to the rural African context. These include: the separation of the supply of pumps from the supply of assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 2 publications
4
79
0
Order By: Relevance
“…By the year 2015, the national water supply and sanitation program under its MDG planned to increase water supply coverage and sanitation by 64% and 54% respectively. It has been said that the chances of achieving the MDG of halving the proportion of people without access to safe water by 2015 will be seriously questioned unless levels of sustainability can be greatly improved [3,4].…”
Section: Background Of the Studymentioning
confidence: 99%
“…By the year 2015, the national water supply and sanitation program under its MDG planned to increase water supply coverage and sanitation by 64% and 54% respectively. It has been said that the chances of achieving the MDG of halving the proportion of people without access to safe water by 2015 will be seriously questioned unless levels of sustainability can be greatly improved [3,4].…”
Section: Background Of the Studymentioning
confidence: 99%
“…The implication is that institutions and actors at all levels need to have the essential capabilities to fulfil their respective roles towards sustainability of the rural water facilities (RWFs) (Litvack et al, 1998;Smoke, 2003Smoke, , 2010Harvey & Reed, 2004;IOB, 2011). Tanzanian villages are diverse in terms of managerial and technical capacity related to water service delivery (Cleaver & Toner, 2006;Jiménez & Pérez-Foguet, 2010a, b).…”
Section: Periodmentioning
confidence: 99%
“…As part of the decentralization process, the current National Water Policy (NAWAPO) requires villagers to contribute money or physical labour to the capital investment, to manage the water schemes, and to take responsibility for O&M (URT, 2002(URT, , 2008. However, studies on rural water in Africa have observed that achieving the required level of RWF sustainability necessitates a clear definition of the roles of each actor and at all levels, as well as the capabilities to perform them (Harvey & Reed, 2004;IOB, 2011). Already in 1988, an evaluation of the Tanzania rural water supply considered capacity building and clearly defined roles of the different actors as essential to improving the sector's policies from the village to the national level (Therkildsen, 1988).…”
Section: Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it has been reported that about 250,000 boreholes have been constructed for use in Africa [7]. Though the purpose of these initiatives is to afford sustainable water supply in terms of quality and quantity, there are many reports of abandonment of some of these facilities in many places [6][7][8][9][10][11]. The reasons assigned to the abandonment include the mechanical breakdown of hand pumps and lack of water in the borehole.…”
Section: Introductionmentioning
confidence: 99%